Índice de geodiversidade do estado de Sergipe - Amorim, Paloma Santos (2023)
Geodiversity can be understood as a spatial variation of abiotic elements such as geology, geomorphology, hydrology and pedology, within nature. It can be studied qualitatively and/or quantitatively, but there are few studies related to the importance of identifying and quantifying abiotic elements. In this sense, the work aims to identify and characterize the elements of geodiversity in the state of Sergipe, from the spatial analysis of the elements that make up the geodiversity index, in order to create a database of possible geosites. The work steps consist of a bibliographic survey, field work in different municipalities and the mapping of geodiversity indices. In this last stage, a map of Sergipe's geodiversity was produced, which resulted from the determination of the diversity of elements in each grid of the systematic articulation of cartographic maps, which were chosen from the study area. The method is based on superimposing a grid over different maps at scales ranging from 1 / 500,000 to 1 / 250,000, and the final Geodiversity Index is the sum of four partial indices calculated on a 5 km grid. With the results of the quantification of the geodiversity of the state of Sergipe, it was observed that most of the high indices are in the agreste of the state, close to the very high areas, as in the Serra de Itabaiana and Serra da Miaba National Parks. With the identification of high index locations, it is intended to obtain future analyzes of areas with potential for valuable elements of geodiversity, with capacity for geotourism exploration. The results of this study can be used for the management of the territory, in geotourism and by the academic community, in addition to helping to support further studies of a local nature (inventory and characterization of geoheritage).